Global research trends in Environmental adaptation techniques focusing on climate change through scientometric lens - G. Shyamala; R. Gobinath; B. Hemalatha; DivyaSri Akkalla; S. Shenbaga Ezhil; V. Sathya (Discover Sustainability)
Abstract Climate change is a significant threat to ecosystems and communities, and challenges global sustainability; therefore, more research on climate change adaptations should be conducted. This scientometric study presents databases on global trends in academic research, specific contributions, and thematic evolution of environmental adaptations to climate change. Using the Scopus database of publications, this study focuses on publications between 2009 (January) and 2024 (August), with an emphasis on the interpretation of primary research interests, authors, contributions from countries, and collaborative networks. According to the findings, there has been a shift in focus to more adaptive management in agricultural and biological diversity practices, with more emphasis on the integration of ecological, technological, and social science disciplines. This work also reveals that countries have gaps in regional research, especially in developing countries, and highlights the need to work collectively across the globe. Through citation analysis, thematic evolution, and future research recommendations, this study enriches the knowledge of the line of research on environmental adaptation and underlines its significance in addressing climate change effects.